Early survival and delayed death of developmentally‐born dentate gyrus neurons. Issue 11 (18th July 2017) - Cahill, Shaina P.; Yu, Ru Qi; Green, Dylan; Todorova, Evgenia V.; Snyder, Jason S.
Abstract: The storage and persistence of memories depends on plasticity in the hippocampus. Adult neurogenesis produces new neurons that mature through critical periods for plasticity and cellular survival, which determine their contributions to learning and memory. However, most granule neurons are generated prior to adulthood; the maturational timecourse of these neurons is poorly understood compared to adult‐born neurons but is essential to identify how the dentate gyrus (DG), as a whole, contributes to behavior. To characterize neurons born in the early postnatal period, we labeled DG neurons born on postnatal day 6 (P6) with BrdU and quantified maturation and survival across early (1 hr to 8 weeks old) and late (2–6 months old) cell ages. We find that the dynamics of developmentally‐born neuron survival is essentially the opposite of neurons born in adulthood: P6‐born neurons did not go through a period of cell death during their immature stages (from 1 to 8 weeks). In contrast, 17% of P6‐born neurons died after reaching maturity, between 2 and 6 months of age. Delayed death was evident from the loss of BrdU + cells as well as pyknotic BrdU + caspase3 + neurons within the superficial granule cell layer. Patterns of DCX, NeuN, and activity‐dependent Fos expression indicate that developmentally‐born neurons mature over several weeks and a sharp peak in zif268 expression at 2 weeks suggests that developmentally‐born neurons mature faster than adult‐born neurons (which peak at 3 weeks). Collectively, our findings are relevant for understanding how developmentally‐born DG neurons contribute to memory and disorders throughout the lifespan. High levels of early survival and zif268 expression may promote learning, while also rendering neurons sensitive to insults at defined stages. Late neuronal death in young adulthood may result in the loss of hundreds of thousands of DG neurons, which could impact memory persistence and contribute to hippocampal/DG atrophy in disorders such as depression.